Marketing digital y posicionamiento de la empresa Das Haus Crew en Iquitos año 2024 - Navarro Moreno, Sergio Daniel (2025)
The research focuses on determining the relationship between digital marketing and the positioning of the company Das Haus Crew 2024. For this purpose, a basic type methodology with a quantitative approach, at a descriptive-correlational level, with a non-experimental design and cross sectional study was used. The population and study sample consisted of 55 frequent customers, and the sampling was census-based. A detailed analysis was carried out, and the general descriptive results obtained determined that Variable 1: Digital Marketing received a rating of 35% in the good category, 51% in the fair category, and 15% in the poor category. Similarly, Variable 2: Positioning received a rating of good in 55%, in the fair category 36%, and 9% in the poor category. In the inferential results, a Pearson correlation coefficient r of 0.861 was recorded with a two-tailed sig. of <0.001, determining a high and significant positive relationship between both variables. This finding supports the importance of strengthening digital marketing strategies to enhance positioning. Therefore, it is affirmed that there is a significant relationship between digital marketing and the positioning of the company Das Hause Crew, year 2024.